Ingestion of xylooligosaccharides during the suckling period improve the feed efficiency and hindgut fermentation capacity of piglets after weaning. Issue 21 (22nd September 2021) - Bai, Yu; Wang, Zhenyu; Zhou, Xingjian; Zhang, Yaowen; Ye, Hao; Wang, Haotian; Pi, Yu; Lian, Shuai; Han, Dandan; Wang, Junjun
Abstract : Fiber ingestion during the suckling period is helpful for gut development and probiotic colonization. Abstract : Fiber ingestion during the suckling period is helpful for gut development and probiotic colonization. Xylooligosaccharides (Xos) and xylan (Xyl) were selected to investigate the effects of different polymerization degree fiber ingestion on the growth performance and microbiota fermentation capacity of pre- and post-weanling piglets. An in vitro fermentation trial was also conducted to verify the microbial fermentation capacity of weanling piglet fecal microbiota. Results showed that Xos and Xyl ingestion had no significant effect on the piglet body weight and d -lactate level in the plasma at 21 d during the suckling period. After weaning, piglets in the Xyl group had a lower average daily gain (ADG) ( P < 0.05), vitro dry matter (DM) fermentability ( P < 0.05) and activity of xylanase ( P < 0.05) than the control and Xos groups. The Xos group had no significant difference in the ADG when compared with the control group, but a significantly lower feed conversion ratio (FCR) ( P < 0.05) than the control group, which means a high feed efficiency in the Xos group. The highest carbohydrate digestion and absorption ability of fecal microbiota ( P < 0.05) was found in the Xos group. Meanwhile, the Xos group had the highest butyrate production ability ( P < 0.05) and activity of xylanase ( P < 0.05) during in vitro fermentation. The ingestion of Xyl during the suckling period had negative effects on the feed efficiency and hindgut fermentation capacity of weanling piglets. Xylooligosaccharide ingestion to suckling piglets improves growth performance and feed efficiency after weaning through increasing the fermentation capacity of microbiota and fiber-degrading enzyme secretion.